Synthesis and Evaluation of Soy Fatty Acid Ester Estolides as Bioplasticizers in Poly(Vinyl Chloride). (27th August 2019) - Stolp, Lucas J.; Joseph, Eugene; Kodali, Dharma R.
Abstract: Plasticizers are nonvolatile organic liquids that impart flexibility to polymers. Due to environmental, health, and safety reasons, the industry is looking for bioplasticizers to replace petroleum‐derived phthalates. To fulfill this need, soy fatty acid ester estolides were synthesized, characterized, and evaluated as phthalate replacements. Soybean oil was transesterified with methanol or glycerol to form lower molecular weight fatty acid esters that were epoxidized and ring opened with acetic acid and acetylated to give the final products. Ring opening and acetylation of the epoxidized oleic acid esters gave acyclic acetate fatty acid ester estolides, whereas the polyunsaturated fatty acid esters, linoleate, and linolenate gave cyclic tetrahydrofuran derivatives and cross‐linked higher molecular weight materials. The cyclization mechanism to form the tetrahydrofuran derivatives was postulated. Soy fatty acid ester estolides were compounded with formulated poly(vinyl chloride), (PVC) and tested for their functional properties. The physical and functional properties of the new bioplasticizers were compared with commercial plasticizers. The elasticity of PVC compounded with experimental plasticizers and commercial phthalates was comparable. PVC compounded with fatty acid methyl ester estolide showed lower glass transition temperature and similar tensile properties compared to PVC compounded with the commercial phthalate. PVC compounded with the glyceryl fatty acid ester estolide showed a higher glass transition temperature, higher tensile properties compared to PVC compounded with the commercial phthalate.